The Stress of the Street for Patients With Persecutory Delusions: A Test of the Symptomatic and Psychological Effects of Going Outside Into a Busy Urban Area. - Freeman, D; Emsley, R; Dunn, G; Fowler, D; Bebbington, P; Kuipers, E; Jolley, S; Waller, H; Hardy, A; Garety, P (2014)
BACKGROUND: For many patients with persecutory delusions, leaving home and going into crowded streets is a key clinical problem. In this study we aimed to inform treatment development by determining the psychological mechanisms whereby busy urban environments increase paranoia. In a randomized design with prespecified mediation analysis, we compared the effects on patients of going outside into a busy social environment with staying inside. METHODS: Fifty-nine patients with current persecutory delusions, in the context of nonaffective psychosis, reporting fears when going outside were assessed on factors from a cognitive model of paranoia. They were then randomized either to enter a busy local shopping street or to complete a neutral task indoors. They were then reassessed on the measures. RESULTS: Compared with staying inside, the street exposure condition resulted in significant increases in paranoia, voices, anxiety, negative beliefs about the self, and negative beliefs about others. There was also a decrease in positive thoughts about the self. There was no alteration in reasoning processes. There were indications that the increase in paranoia was partially mediated by increases in anxiety (45%), depression (38%), and negative beliefs about others (45%). CONCLUSIONS: We found that increases in negative affect may form an important route by which social exposure in urban environments triggers paranoid thoughts. The study provides an illustration of how an experimental approach can be applied to help understand a specific difficulty for patients with psychosis. In future studies the effects of specific elements of the social environment could be tested.